2016
DOI: 10.5433/1679-0359.2016v37n5p3327
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile of broilers fed diets with inclusion of mango waste meal

Abstract: We evaluated the effect of including 2.5, 5.0, 7.5 and 10.0% mango waste meal (MWM) variety UBA in corn and soybean meal-based diet on the serum lipid profile of broilers. The experimental design was completely randomized, with five treatments and six replicates with 20 birds per experimental unit. Concentrations of creatinine, albumin, total protein, total cholesterol, triacylglycerols (TAG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and very-low-density lipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…The latter condition may suggest that feeding fermented feed shifted the metabolic process from fat synthesis to fatty acid β-oxidation and tissue protein synthesis. In agreement with our inference, Vieira et al [26] reported the inverse relationship between serum albumin and triglycerides levels in broilers fed mango waste meal at 42 days of age. However, our inference must be taken with care as the increased albumin level was not capable of increasing the total protein in the serum of the respective birds.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The latter condition may suggest that feeding fermented feed shifted the metabolic process from fat synthesis to fatty acid β-oxidation and tissue protein synthesis. In agreement with our inference, Vieira et al [26] reported the inverse relationship between serum albumin and triglycerides levels in broilers fed mango waste meal at 42 days of age. However, our inference must be taken with care as the increased albumin level was not capable of increasing the total protein in the serum of the respective birds.…”
Section: Resultssupporting
confidence: 93%
“…However, our inference must be taken with care as the increased albumin level was not capable of increasing the total protein in the serum of the respective birds. The same condition was actually found in the study of Vieira et al [26], in which the albumin level was not in parallel with the total protein levels in the serum of broilers. Our present finding showed that serum globulin level was lower (p<0.05) in FERB than that in BACI, but did not differ from that in CONT and FERM broilers.…”
Section: Resultssupporting
confidence: 83%